Pemberian Edukasi Perilaku Hidup Bersih dan Sehat di Desa Gunung Menang Kecamatan Penukal Kabupaten Penukal Abab Lematang Ilir - Ranida Arsi; Putri Ayu Eem MS; Verdia Nabilah; Holifah Holifah; Siti Hana Khayyirah; Ernima Yusnita; Amalia Aini Sapitri; Anisa Fitri; Amanda Febrianti; Gerry Akino; M Ridho Alfarabi; Siti Sholehah; Nina Nurfala; Melati Rias Susanto; Sri Ekawati; Risna Maryana; Putri Zuliana (JURNAL PENGABDIAN KADER BANGSA, 2025)
Clean and Healthy Living Behavior (PHBS) is the embodiment of a health-oriented lifestyle within the culture of people, families, and communities, with the objective of enhancing, preserving, and safeguarding their physical, mental, spiritual, and social well-being. Gunung Menang Village confronts issues pertaining to environmental hygiene and the effects of both environmental and personal sanitation. This research seeks to analyze the many educational initiatives implemented to mitigate these issues in this town. This research employs a health education approach including counseling and collaborative activities. The study's results demonstrate that education including the roles of families and communities significantly enhances knowledge about the necessity of health and hygiene maintenance. This research advocates for a better organized and collaborative educational program among schools and communities in Gunung Menang Village